FINDING HUMAN RIGHTS CONSENSUS: INDONESIA AS CONSTRUCTIVE FORCE IN AICHR - Dinna Prapto Raharja (Universitas Jenderal Ahmad Yani, 2022)
Finding consensus has been argued as a stumbling block for actions in ASEAN, including in ASEAN’s Human Rights Body: the AICHR (ASEAN Intergovernmental Commission on Human Rights). While past studies discussed the limits of consensus making in ASEAN, there is lacunae of research on the institutional performance pressure to get things done in an intergovernmental setting and the impacts of diverse mandates among AICHR Representatives to finding human rights consensus. There are at least four types of approaches that has been employed by AICHR Representatives to find consensus where the constructivist and pragmatist collided, but it becomes clear that the challenge is cross-sectoral rather than merely internal AICHR, which makes it imperative to assess the direction for ASEAN’s institutional performance when evaluating consensus building.